STRATEGI BMT JAMA’AH AL-AMANAH DALAM MENINGKATKAN EKONOMI MASYARAKAT DI KECAMATAN KOTO TANGAH KOTA PADANG - Kasmir Kasmir; Jusmawati Jusmawati; Azizah Fitrah (Universitas Islam Negeri Imam Bonjol Padang, 2019)
The background of this research is the priority of the community to carry out savings and loans in BMT. Limited budget so it does not meet the needs. Lack of enthusiasm for human resources because it is accepted that those who do not meet the needs. The formulation of this research problem is the BMT strategy of Al Jamaah Al-Amanah in improving the community's economy in the Koto Tangah District of Padang City? The purpose of this study 1). To find out the strategy in formulating a plan that will be implemented. 2). To find out the strategy in implementing the program that has been formulated. 3). To learn the strategies in the evaluation of programs that have been implemented. The research method used is a qualitative method using descriptive. While data collection techniques and tools use observation, interviews and documentation studies. Data management is done by qualitative descriptive analysis techniques, then compared / opened data. The results showed that: a. a strategy in formulating a plan that will be implemented to collect and channel funds with a fair profit sharing system, b. Strategies in the implementation of the program are formulated as productive financing, both intended as working capital and investment, the public can choose the BMT financing model. The BMT financing model Jama'ah Al-Amanah can be used for sharia and Mudarabah Strategies in the evaluation program that has been implemented in the form of maximizing consumer satisfaction. choice (product range). Supports life by providing various pleasures